The grinding behavior of ground copper powder for Cu/CNT nanocomposite fabrication by using the dry grinding process with a high-speed planetary ball mill - Choi, Heekyu; Bor, Amgalan; Sakuragi, Shiori; Lee, Jehyun; Lim, Hyung-Tae (Journal of the Korean Physical Society, 2016)
The behavior of ground copper powder for copper-carbon nanotube (copper-CNT) nanocomposite fabrication during high-speed planetary ball milling was investigated because the study of the behavior characteristics of copper powder has recently gained scientific interest. Also, studies of Cu/CNT composites have widely been done due to their useful applications to enhanced, advanced nano materials and components, which would significantly improve the properties of new mechatronics-integrated materials and components. This study varied experimental conditions such as the rotation speed and the grinding time with and without CNTs, and the particle size distribution, median diameter, crystal structure and size, and particle morphology were monitored for a given grinding time. We observed that pure copper powders agglomerated and that the morphology changed with changing rotation speed. The particle agglomerations were observed with maximum experiment conditions (700 rpm, 60 min) in this study of the grinding process for mechanical alloys in the case of pure copper powders because the grinding behavior of Cu/CNT agglomerations was affected by the addition of CNTs. Indeed, the powder morphology and the crystal size of the composite powder could be changed by increasing the grinding time and the rotation speed.